Severe anaphylactic reaction to patent blue in breast cancer surgery - Haddad, Cássio Furtini; Ferreira, Debora Murad; Cortez, Isabela Lima; Vicente, Arthur José de Oliveira; Silva, Alex Amaral Gomes; Naback, Carolina Pinheiro (Mastology, 2020)
Sentinel lymph node biopsy in the surgical treatment of initial breast cancer has been increasingly adopted to assess axillary status as a way to replace total lymphadenectomy. The sentinel lymph node can be identified using coloring agents or radiopharmaceuticals. In Brazil, patent blue is the most used dye for this type of procedure, with high rates of identification and safety; however, in some cases, the use of this substance can lead to the occurrence of anaphylactic reactions. The case presented here refers to a 41-year-old female patient admitted for a surgical procedure for total mastectomy associated with sentinel lymph node biopsy with patent blue. After surgical initiation, the patient developed severe anaphylactic shock, staying 21 days in the intensive care unit (ICU) for recovery. Most anaphylactic reactions that occur in the transoperative period are mediated by IgE antibodies, resulting in the degranulation of mast cells and basophils, with the release of mediators such as histamine, prostaglandins, proteoglycans, and cytokines, leading to the clinical manifestations of anaphylaxis. There is evidence that part of the population is allergic to patent blue, and may present with manifestations ranging from hives and pruritus to severe cardiovascular collapse, requiring hospitalization in an ICU. The purpose of this article was to report a case of severe anaphylactic reaction to patent blue and to review the literature regarding this infrequent and potentially serious situation.